Solid Concentration Effect for Solvent Extraction Process of Oily Contaminated Soil - Lely Fitriyani; Edwan Karadena; Sukandar Sukandar (Reaktor, 2019)
Solvent extraction has been used as a method to wash oil content of oily contaminated soil in industry for years. Some solvents and temperature ranges has been chosen to increase the oil recovery rate of extraction process, however only few studies reported that it has been able to reach remaining Total Petroleum Hydrocarbon (TPH) less than 0.5% in less than 30 minutes. During the experiments, acetone and toluene chosen to extract oil content from contaminated soil by using solvent extraction process. Temperature selected were between 24°C up to 70°C. Mixing apparatus which has been utilized was centrifugation machine with 1000 rpm (1570 g) operational speed. Duration of treatment process was 10 minutes with some variations of solid to solvent ratio. During the experiments, it was observed that by using toluene and acetone as solvents, the optimum Total Petroleum Hydrocarbon (TPH) removal obtained at temperature 50°C. In the other hand, optimum solid to solvent ratio toluene ratio was 1:6. As a solvent acetone observed capable to reduce TPH content until below 0.5% as threshold limit for TPH of contaminated soil regulated by environmental regulation in Indonesia. During the experiments it was also observed the dependency of solid concentration (Cs) with dissociation coefficient (KD). In the other hand, heavy metal at the remaining extracted soil after soil washing was observed available in safe concentration to be discharged to the environment base on regulation in Indonesia. Keywords: solvent extraction, soil washing, contaminated soil, TPH, centrifugation, oil sludge, acetone, toluene, solid treatment.